Polycarbonate composition having high CTI

A thermoplastic composition combining aromatic polycarbonate, (meth)acrylate copolymer, phosphorus-containing flame retardant, and fluorine-containing antidrip agent addresses the low CTI and moderate flame retardancy of polycarbonate-based materials, achieving high CTI and UL94 classification V0 for safe and compact high voltage applications.

JP2025510772APending Publication Date: 2025-04-15COVESTRO DEUTSCHLAND AG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024556391
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-25
Filing Date
2023-03-20
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Polycarbonate-based thermoplastic compositions have a low comparative tracking index (CTI) and moderate flame retardancy, which is insufficient for high voltage applications in the electrical and electronic sector, requiring materials with high CTI and UL94 classification V0 for safety and compact design.

Method used

A thermoplastic composition comprising at least 68% by weight of aromatic polycarbonate, 4% to 25% by weight of (meth)acrylate copolymer, 2% to 10% by weight of phosphorus-containing flame retardant, and 0.25% to 2% by weight of fluorine-containing antidrip agent, specifically designed to achieve high CTI and UL94 classification V0, while maintaining good heat deformation resistance.

Benefits of technology

The composition achieves a high comparative tracking index of at least 600V and UL94 classification V0 at 2 mm thickness, ensuring safety and compact design in high voltage applications, while also maintaining good heat deformation resistance with a Vicat softening temperature of at least 105°C.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025510772000001
    Figure 2025510772000001
  • Figure 2025510772000002
    Figure 2025510772000002
  • Figure 2025510772000003
    Figure 2025510772000003
Patent Text Reader

Abstract

Described is a thermoplastic composition based on aromatic polycarbonate having a high comparative tracking index, good flame retardancy, and high heat distortion temperature. The composition contains a combination of a (meth)acrylate copolymer, a phosphorus-containing flame retardant, and a fluorine-containing anti-drip agent.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to flame retardant thermoplastic compositions based on polycarbonate having a high comparative tracking index. [Background technology]

[0002] Polycarbonate offers many advantages over other thermoplastic polymers due to its high impact strength, high heat distortion resistance, and certain inherent flame retardancy. Due to this unique property profile, polycarbonate compositions are suitable for a variety of different applications, for example in the field of electrical and electronic components. In particular, good insulating properties and high flame retardancy are essential safety-related basic requirements for materials used in this field. In applications where plastics are in direct contact with conductor paths, high resistance to tracking currents under voltage load is a prerequisite, so that there are no short circuits in the components and therefore no fires.

[0003] Comparative Tracking Index (CTI) generally describes the resistance of plastic materials to environmental influences. The CTI value is a measure of the tendency of plastics to form conductive paths on the surface under voltage and promote the generation of electrical tracking currents under the influence of environmental influences, such as moisture and pollution. The higher the tracking current resistance of a material, i.e. the higher its Comparative Tracking Index (CTI value), the better it is suitable for use in high voltage applications, such as modern electromobility applications. Another advantage of materials with high CTI values ​​is that in electronic components, conductor paths can be placed closer together without risk of short circuits, which in turn allows for reduced component dimensions and therefore more compact designs and weight savings.

[0004] In contrast to other thermoplastic polymers, such as polystyrene, polyesters, etc., polycarbonate has a very low comparative tracking index and a moderate flame retardancy by itself. Due to the high proportion of aromatic structures, polycarbonate has a relatively high tendency to char. The CTI of pure polycarbonate is about 250V or even lower (Non-Patent Document 1). However, for many applications in the electronic / electrical (EE) sector, such as the electromobility sector, for safety reasons, a high CTI is required for the materials used, typically 600V (corresponding to insulating material group PLC 0 according to EN 50124). At the same time, the materials must have a high flame retardancy, i.e. classification V0 according to UL 94V, even in particular at low wall thicknesses.

[0005] Pure polycarbonate typically already has a certain inherent flame retardancy (classification V2 according to UL 94 V), which is insufficient for most applications in the EE sector. In order to achieve the required classification V0 according to UL 94 V, the addition of suitable flame retardants is required. Typically employed in polycarbonates are halogenated sulfonic acid compounds (e.g. Rimar salts (potassium perfluorobutanesulfonate, C4 salts) or KSS salts (potassium diphenylsulfone-3-sulfonate)), or also organophosphate compounds (e.g. bisphenol A bis(diphenylphosphate) (BDP), resorcinol bis(diphenylphosphate) (RDP)), or phosphazenes. The mechanism of action of such flame retardants is based on the formation of a solid charred surface layer that blocks the oxygen supply and thus inhibits the combustion process.

[0006] The effect that forms the basis of a good comparative tracking index is, among other things, a low tendency to form conductive paths on the surface, which is the exact opposite of the "charring" mechanism of action of surface active flame retardants and therefore poses special challenges in controlling the CTI and flame retardancy. [Prior art documents] [Non-patent literature]

[0007] [Non-Patent Document 1] F. Acquasanta et al., Polymer Degradation and Stability, 96 (2011), 2098-2103 Summary of the Invention

[0008] The aim was therefore to provide polycarbonate-based compositions which achieve UL 94 classification V0 at 2 mm, particularly preferably at 1.5 mm, and which have a high comparative tracking index, preferably specified according to the rapid test method according to IEC 60112:2009, at least 400 V, preferably 600 V. Due to the field of application and the heat development in EE parts, the compositions should also preferably have a good heat distortion resistance, in particular a Vicat softening temperature, specified according to ISO 306:2014-3, VST method B, of at least 105° C., particularly preferably at least 108° C. Furthermore, the CTI should preferably be robust, i.e. a high CTI should be reliably achieved at different working voltages, for example 600 V, but also 300 V or 350 V.

[0009] Surprisingly, it has been found that this property profile is achieved by a special combination of aromatic polycarbonate in combination with certain amounts of a (meth)acrylate copolymer and a phosphorus-containing flame retardant and a fluorine-containing anti-drip agent.

[0010] Accordingly, the present invention provides a thermoplastic composition comprising: A) at least 68% by weight of an aromatic polycarbonate; B) 4% by weight to 25% by weight of a (meth)acrylate copolymer containing aromatic (meth)acrylate units b1 and methyl methacrylate units b2 in a weight ratio b1 / b2 of (5% by weight to 20% by weight) / (80% by weight to 95% by weight) based on the total weight of the (meth)acrylate copolymer; C) 2% by weight to 10% by weight of a phosphorus-containing flame retardant; D) 0.25% by weight to 2% by weight of a fluorine-containing drip prevention agent containing polytetrafluoroethylene; E) optionally one or more additional additives selected from the group consisting of one or more mold release agents, heat stabilizers, antioxidants, dyes, pigments, ultraviolet absorbers, infrared absorbers, impact modifiers, antistatic agents, optical brighteners, hydrolysis stabilizers, ester interchange stabilizers, compatibilizers, laser marking additives, and mixtures thereof; Contains Weight percent figures are based on the total composition unless otherwise indicated. the ratio of the amount of (meth)acrylate copolymer in weight percent to the amount of phosphorus-containing flame retardant in weight percent is less than or equal to 2.5, and the ratio of the amount of (meth)acrylate copolymer in weight percent to the amount of polytetrafluoroethylene in weight percent is less than or equal to 20; The thermoplastic composition does not contain a flame retardant selected from the group consisting of alkali metal salts, alkaline earth metal salts and ammonium salts of aliphatic or aromatic sulfonic acid, sulfonamide and sulfonimide derivatives. A thermoplastic composition is provided.

[0011] It will be understood that all components present in the compositions according to the present invention add up to 100% by weight. When a numerical range has an upper limit indicated by "~X", this includes the stated numerical value and any upward rounding range.

[0012] The total amount of the (meth)acrylate copolymer in the composition according to the present invention is 4% by weight to 25% by weight.

[0013] It will be understood that the components used may contain typical impurities, for example impurities resulting from their manufacturing process. It is preferred to use components with the highest possible purity. It will further be understood that such impurities may be present even in the event of a limiting expression of the composition.

[0014] The present invention also provides moldings made from the thermoplastic composition according to the invention, i.e. moldings that consist only of the thermoplastic composition according to the invention or that contain areas made of the thermoplastic composition according to the invention. Such moldings are in particular those for which the above-mentioned property profile is particularly attractive, i.e. moldings that are part of components in the EE sector, in particular high-voltage switches, inverters, relays, electronic connectors, electrical connectors, circuit breakers, components for photovoltaic applications, electric motors, heat sinks, chargers and charging plugs for electric vehicles, electrical junction boxes, smart meter housings, miniature circuit breakers, busbars. The components are preferably designed for a working voltage of at least 400V. For this purpose, the materials expediently used preferably have a comparative tracking index of at least 600V, as specified according to the rapid test method according to IEC 60112:2009 as described above.

[0015] The compositions according to the invention do not show any significant tracking current (more than 0.5 A for 2 seconds) even when subjected to at least 50 drops of 0.1% ammonium chloride solution at 375 V, more preferably at 400 V, particularly preferably at 600 V, preferably according to the rapid test method according to IEC 60112:2009 and described in the description section. At the same time, the compositions according to the invention have a flame retardancy of V0 according to UL 94 V with a test specimen thickness of 2 mm. In addition to a high CTI and good flame retardancy, the compositions preferably also have good heat distortion resistance, which is expressed by a Vicat softening temperature of at least 105°C, more preferably at least 110°C ± 2°C, as specified according to ISO 306:2014-3, VST method B.

[0016] Therefore, the present invention also provides the use of 4% by weight to 25% by weight, preferably 5% by weight to 25% by weight, of a (meth)acrylate copolymer containing aromatic (meth)acrylate units b1 and methyl methacrylate units b2 in a weight ratio b1 / b2 of (5% by weight to 20% by weight) / (80% by weight to 95% by weight) based on the total weight of the (meth)acrylate copolymer, 2% by weight to 10% by weight of a phosphorus-containing flame retardant, and 0.25% by weight to 2% by weight of a fluorine-containing anti-drip agent containing polytetrafluoroethylene, in a thermoplastic composition based on an aromatic polycarbonate, in particular a thermoplastic composition based on a bisphenol A homopolycarbonate, for achieving a high CTI of 600V and a UL94 classification of V0 at a test piece thickness of 2 mm, the weight percentage figures being based on the entire composition obtained. The proportion of aromatic polycarbonate, preferably bisphenol A homopolycarbonate, in the entire composition obtained here is preferably at least 68% by weight, the ratio of the amount of (meth)acrylate copolymer in weight % to the amount of phosphorus-containing flame retardant in weight % is 2.5 or less, and the ratio of the amount of (meth)acrylate copolymer in weight % to the amount of polytetrafluoroethylene in weight % is 20 or less.

[0017] Such a specific use exists, for example, when the corresponding composition is used for an insulating layer that requires a CTI of 600V for the application. Such an insulating layer can be provided, for example, on an inverter as a layer for protection against external influences. For inverters, the standard insulating material has a CTI of 600V. The composition according to the invention can also be used as an insulating layer for other electrical components, for example transistors. The electrical components of the transistor are protected by overmolding a plastic with a high CTI. This plastic protects the electrical components both from contact and from undesired electrical interaction with adjacent metal parts or electrical components, such as metal heat sinks.

[0018] Due to the high heat generated during operation, transistors are often applied directly to a heat sink, and here too the thermoplastic composition according to the invention introduced between the heat sink and the transistor ensures safe operation.

[0019] A further field of use are mounting brackets for busbars, where materials with a high CTI must be used as well. The mounting brackets essentially have two functions: fixing the busbars in an assembly group to prevent any position changes during operation, and acting as a spacer to allow several busbars to be juxtaposed, where again a sufficiently large distance must be selected between the two busbars to prevent sparks through the air. However, in addition, tracking on the surface of the mounting bracket must be prevented, not only between the busbars, but also between the busbars and other metal parts, for example the screws for fixing the mounting bracket to the structure below. Mounting brackets with a high CTI can increase the component density and energy density here.

[0020] For plug connectors, plug devices and sockets, there is a high risk of tracking currents occurring, which can lead to electrical failures and possible fires. Enclosures that enclose the current-carrying wires can improve the situation, as they have a lower risk of contamination. Plug connectors for chargers, or USB-C plug connectors, are at a higher risk, as they cannot cover or enclose the current-carrying conductor tracks and are further exposed to contamination such as sweat, moisture, fabric particles, dust and other materials. High CTI materials are needed to provide sufficient protection from tracking, but also to allow for miniaturization or increased power density.

[0021] Naturally, the features mentioned as being preferred, particularly preferred etc. for the composition also apply in relation to the uses according to the invention.

[0022] The individual components of the composition according to the invention are described in more detail hereinafter:

[0023] Ingredient A Component A of the composition according to the invention is an aromatic polycarbonate.

[0024] Aromatic polycarbonates in the context of the present invention include not only homopolycarbonates but also copolycarbonates and / or polyestercarbonates. The polycarbonates can be linear or branched in a known manner. Polycarbonate mixtures can also be used according to the present invention.

[0025] The thermoplastic polycarbonates, including thermoplastic aromatic polyester carbonates, preferably have a weight average molecular weight M w is 15000 g / mol to 40000 g / mol, more preferably 34000 g / mol, particularly preferably 17000 g / mol to 33000 g / mol, and particularly preferably 19000 g / mol to 32000 g / mol; w is determined by gel permeation chromatography using dichloromethane as eluent and calibrated against bisphenol A polycarbonate standards, using linear polycarbonate (formed from bisphenol A and phosgene) of known molar mass distribution from PSS Polymer Standards Service GmbH, Germany, using calibration according to method 2301-0257502-09D (2009 German edition) from Currenta GmbH & Co. OHG, Leverkusen. The eluent is dichloromethane. The column combination is a crosslinked styrene-divinylbenzene resin. Analytical column diameter: 7.5 mm; length: 300 mm. Column material particle size: 3 μm-20 μm. Solution concentration: 0.2 wt.%. Flow rate: 1.0 ml / min, solution temperature: 30°C. UV and / or RI detection is used.

[0026] The melt volume flow rate (MVR) of the aromatic polycarbonate used is specified according to ISO 1133:2012-03 at a test temperature of 300°C and a load of 1.2 kg, preferably at 5 cm 3 / (10 minutes)~35cm 3 / (10 min), more preferably 6 cm 3 / (10 minutes)~25cm 3 / (10 min), and even more preferably 6 cm 3 / (10 minutes)~21cm 3 / (10 minutes).

[0027] A maximum of 80 mol %, preferably 20 mol % to 50 mol %, of the carbonate groups of the polycarbonates used according to the invention can be replaced by aromatic dicarboxylic acid ester groups. Polycarbonates of this type, which have acid radicals derived from aromatic dicarboxylic acids as well as from carbonic acid introduced into the molecular chain, are called aromatic polyester carbonates. For the purposes of the present invention, they are encompassed by the general term "thermoplastic aromatic polycarbonates".

[0028] The details of polycarbonate preparation have been described in numerous patent specifications over the past 40 years or so. In this specification, the following may be mentioned by way of example: Schnell, "Chemistry and Physics of Polycarbonates", Polymer Reviews, Volume 9, Interscience Publishers, New York, London, Sydney 1964, D. Freitag, U. Grigo, PR Mueller, H. Nouvertne, BAYER AG, "Polycarbonates" in Encyclopedia of Polymer Science and Engineering, Volume 11, Second Edition, 1988, pages 648-718, and finally U. Grigo, K. Kirchner and PR Mueller "Polycarbonate" [Polycarbonates] in Becker / Braun, Kunststoff-Handbuch [Plastics Handbook], volume 3 / 1, Polycarbonate, Polyacetale, Polyester, Celluloseester [Polycarbonates, Polyacetals, Polyesters, Cellulose Esters], Carl Hanser Verlag Munich, Vienna 1992, pages 117 to 299.

[0029] Aromatic polycarbonates are prepared, for example, by the interfacial process, by reaction of dihydroxyaryl compounds with carbonyl halides, preferably phosgene, and / or aromatic dicarbonyl dihalides, preferably benzene dicarbonyl dihalides, optionally using chain reaction terminators and optionally using trifunctional or higher branching agents. Also possible is the preparation by reaction of dihydroxyaryl compounds with, for example, diphenyl carbonate, via melt polymerization methods.

[0030] For the preparation of polyester carbonates, a portion of the carbonic acid derivatives is replaced with aromatic dicarboxylic acids or dicarboxylic acid derivatives, specifically aromatic dicarboxylic ester structural units according to the carbonate structural units to be replaced in the aromatic polycarbonate.

[0031] Dihydroxyaryl compounds suitable for the preparation of polycarbonates are of formula (1) HO-Z-OH (1), During the ceremony, Z is an aromatic radical having 6 to 30 carbon atoms, which may have one or more aromatic rings, which may be substituted, and which may have aliphatic or alicyclic radicals or alkylaryl or heteroatoms as bridging elements.

[0032] Suitably, Z in formula (1) is a radical of formula (2): [ka] During the ceremony, R 6 and R 7 are independently H, C1 to C 18 -Alkyl, C1-C 18 -alkoxy, halogen such as Cl or Br, or, in each case, optionally substituted aryl or aralkyl, preferably H or C1-C 12 -alkyl, particularly preferably H or C1-C8-alkyl, especially preferably H or methyl, X is a single bond, -SO2-, -CO-, -O-, -S-, C1-C6-alkylene, C2-C5-alkylidene or C5-C6-cycloalkylidene, which can be substituted by C1-C6-alkyl, preferably methyl or ethyl, or C6-C 12 -arylene, which may be optionally fused to a further aromatic ring containing a heteroatom.

[0033] X is preferably a single bond, C1-C5-alkylene, C2-C5-alkylidene, C5-C6-cycloalkylidene, -O-, -SO-, -CO-, -S-, -SO2- or a radical of formula (3). [ka]

[0034] Examples of dihydroxyaryl compounds include: dihydroxybenzene, dihydroxydiphenyl, bis(hydroxyphenyl)alkanes, bis(hydroxyphenyl)cycloalkanes, bis(hydroxyphenyl)aryls, bis(hydroxyphenyl)ethers, bis(hydroxyphenyl)ketones, bis(hydroxyphenyl)sulfides, bis(hydroxyphenyl)sulfones, bis(hydroxyphenyl)sulfoxides, 1,1'-bis(hydroxyphenyl)diisopropylbenzene, and their ring-alkylated and ring-halogenated compounds.

[0035] Dihydroxyaryl compounds suitable for the preparation of polycarbonates include, for example, hydroquinone, resorcinol, dihydroxydiphenyl, bis(hydroxyphenyl)alkanes, bis(hydroxyphenyl)cycloalkanes, bis(hydroxyphenyl)sulfides, bis(hydroxyphenyl)ethers, bis(hydroxyphenyl)ketones, bis(hydroxyphenyl)sulfones, bis(hydroxyphenyl)sulfoxides, α,α'-bis(hydroxyphenyl)diisopropylbenzene, phthalimidines derived from isatin or phenolphthalein derivatives, and their ring-alkylated, ring-arylated, and ring-halogenated compounds.

[0036] Suitable dihydroxyaryl compounds are 4,4'-dihydroxydiphenyl, 2,2-bis(4-hydroxyphenyl)propane (bisphenol A), 2,4-bis(4-hydroxyphenyl)-2-methylbutane, 1,1-bis(4-hydroxyphenyl)-p-diisopropylbenzene, 2,2-bis(3-methyl-4-hydroxyphenyl)propane, dimethylbisphenol A, bis(3,5-dimethyl-4-hydroxyphenyl)methane, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, bis(3,5-dimethyl-4-hydroxyphenyl)sulfone, 2,4-bis(3,5-dimethyl-4-hydroxyphenyl)-2-methylbutane, 1,1-bis(3,5-dimethyl-4-hydroxyphenyl)-p-diisopropylbenzene, and 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, as well as the following dihydroxyaryl compounds (I) to (III): [ka] In the formula, each R' is a C1-C4-alkyl radical, an aralkyl radical or an aryl radical, preferably a methyl radical or a phenyl radical, particularly preferably a methyl radical.

[0037] Particularly preferred dihydroxyaryl compounds are 2,2-bis(4-hydroxyphenyl)propane (bisphenol A), 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 4,4'-dihydroxydiphenyl, and dimethylbisphenol A, as well as bisphenols of formula (I), formula (II), and formula (III).

[0038] These and other suitable dihydroxyaryl compounds are described, for example, in U.S. Pat. Nos. 3,028,635, 2,999,835, 3,148,172, 2,991,273, 3,271,367, 4,982,014 and 2,999,846, in DE-A-1,570,703, DE-A-2,063,050, DE-A-2,036,052, DE-A-2,211,956 and DE-A-3,832,396, in FR-A-1,561,518 and in the research article "H. Schnell, Chemistry and Physics of Polycarbonates, Interscience Publishers, New York, 1989, 1991, and 1998. 1964", as well as in JP-A-1986-62039, JP-A-1986-62040, and JP-A-1986-105550.

[0039] In the case of homopolycarbonates, only one type of dihydroxyaryl compound is used, whereas in the case of copolycarbonates, two or more types of dihydroxyaryl compounds are used.

[0040] Examples of suitable carbonic acid derivatives are phosgene or diphenyl carbonate.

[0041] Suitable chain terminators that can be used in the preparation of the polycarbonates are monophenols. Examples of suitable monophenols include phenol itself, alkylphenols such as cresol, p-tert-butylphenol, cumylphenol, and also mixtures thereof.

[0042] Suitable chain terminators include one or more linear or branched, preferably unsubstituted, C1-C 30 -alkyl radical- or tert-butyl-substituted phenol. Particularly suitable chain terminators are phenol, cumylphenol, and / or p-tert-butylphenol.

[0043] The amount of chain terminator used is preferably 0.1 mol% to 5 mol%, based on the moles of dihydroxyaryl compound used in each case. The chain terminator can be added before, during or after the reaction with the carbonic acid derivative.

[0044] Suitable branching agents are trifunctional or higher compounds known in polycarbonate chemistry, especially those having three or more phenolic OH groups.

[0045] Examples of suitable branching agents include 1,3,5-tri(4-hydroxyphenyl)benzene, 1,1,1-tri(4-hydroxyphenyl)ethane, tri(4-hydroxyphenyl)phenylmethane, 2,4-bis(4-hydroxyphenylisopropyl)phenol, 2,6-bis(2-hydroxy-5'-methylbenzyl)-4-methylphenol, 2-(4-hydroxyphenyl)-2-(2,4-dihydroxyphenyl)propane, tetra(4-hydroxyphenyl)methane, tetra(4-(4-hydroxyphenylisopropyl)phenoxy)methane, and 1,4-bis((4',4''-dihydroxytriphenyl)methyl)benzene, and 3,3-bis(3-methyl-4-hydroxyphenyl)-2-oxo-2,3-dihydroindole.

[0046] Whatever branching agent is used, its amount is preferably between 0.05 mol % and 2.00 mol %, based on the moles of dihydroxyaryl compound used in each case.

[0047] The branching agent can either be an initial charge together with the dihydroxyaryl compound and the chain terminator in the aqueous alkaline phase, or it can be added dissolved in an organic solvent prior to the phosgenation. In the case of the transesterification process, the branching agent is used together with the dihydroxyaryl compound.

[0048] Particularly suitable polycarbonates are homopolycarbonates based on bisphenol A, homopolycarbonates based on 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, and copolycarbonates based on the two monomers bisphenol A and 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane or based on the two monomers bisphenol A and 4,4'-dihydroxydiphenyl, as well as polycarbonates of formula (I), formula (II), and / or formula (III): [ka] where each R' is C1-C4-alkyl, aralkyl or aryl, preferably methyl or phenyl, especially preferably methyl, and in particular homo- or copolycarbonates derived from dihydroxyaryl compounds, in particular from bisphenol A. Especially preferably, the aromatic polycarbonate comprises a bisphenol A-based homopolycarbonate. Very preferably, the aromatic polycarbonate is a bisphenol A-based homopolycarbonate.

[0049] The total proportion of monomer units based on formula (I), formula (II), formula (III), 4,4'-dihydroxydiphenyl and / or bisphenol TMC in the copolycarbonate, when such a polycarbonate is used, is preferably 0.1 mol % to 88 mol %, particularly preferably 1 mol % to 86 mol %, especially preferably 5 mol % to 84 mol %, in particular 10 mol % to 82 mol % (based on the sum of the moles of the dihydroxyaryl compounds used).

[0050] The relative solution viscosity of the copolycarbonates, as specified according to ISO 1628-4:1999, is preferably in the range of 1.15 to 1.35.

[0051] The dihydroxyaryl compounds used, as well as all other chemicals and auxiliaries added in the synthesis, may be contaminated with contaminants from their own synthesis, handling, and storage, however, it is desirable to use raw materials with the highest possible purity.

[0052] Also suitable are copolycarbonates prepared using diphenols of general formula (4a) [ka] During the ceremony, R 5 is hydrogen or C1-C4-alkyl, C1-C3-alkoxy, preferably hydrogen, methoxy or methyl, R 6 , R 7 , R 8 , and R 9 are each independently C1-C4 alkyl or C6-C 12 -aryl, preferably methyl or phenyl; Y is a single bond, -SO2-, -S-, -CO-, -O-, C1-C6-alkylene, C2-C5-alkylidene, C6-C 12 -arylene, which can optionally be fused to a further aromatic ring containing heteroatoms, or a C5-C6-cycloalkylidene radical, which can be mono- or polysubstituted by C1-C4-alkyl, preferably a single bond, -O-, isopropylidene, or a C5-C6-cycloalkylidene radical, which can be mono- or polysubstituted by C1-C4-alkyl, V is oxygen, C2-C6-alkylene or C3-C6-alkylidene, preferably oxygen or C3-alkylene; p, q, and r are each independently 0 or 1; When q=0, W is a single bond, and when q=1 and r=0, W is oxygen, C2-C6-alkylene, or C3-C6-alkylidene, preferably oxygen or C3-alkylene; when q=1 and r=1, W and V are each independently C2-C6-alkylene or C3-C6-alkylidene, preferably C3-alkylene; Z is C1-C6-alkylene, preferably C2-alkylene; o is the average number of repeating units from 10 to 500, preferably from 10 to 100; m is the average number of repeating units of 1 to 10, preferably 1 to 6, more preferably 1.5 to 5. It is likewise possible to use diphenols in which two or more siloxane blocks of the general formula (4a) are joined together via terephthalic acid and / or isophthalic acid to form ester groups.

[0053] Particular preference is given to (poly)siloxanes of the formulae (5) and (6), [ka] in which R1 is hydrogen, C1-C4-alkyl, preferably hydrogen or methyl, particularly preferably hydrogen, each R2 is independently aryl or alkyl, preferably methyl; X is a single bond, -SO2-, -CO-, -O-, -S-, C1-C6-alkylene, C2-C5-alkylidene, or C6-C 12 -arylene, which can be optionally fused with a further aromatic ring containing a heteroatom; X is preferably a single bond, C1-C5-alkylene, C2-C5-alkylidene, C5-C 12 -cycloalkylidene, -O-, -SO-, -CO-, -S-, -SO2-, and particularly preferably, X is a single bond, isopropylidene, C5 to C 12 -cycloalkylidene or oxygen, particularly preferably isopropylidene, n is an average number of 10 to 400, preferably 10 to 100, particularly preferably 15 to 50; m is an average number of 1 to 10, preferably 1 to 6, and particularly preferably 1.5 to 5.

[0054] The siloxane blocks may likewise preferably be derived from the following structure: [ka] In the formulae (IV), (V), and (VI), a is an average number of 10 to 400, preferably 10 to 100, and particularly preferably 15 to 50.

[0055] It is also preferred that at least two identical or different siloxane blocks of general formula (IV), general formula (V) or general formula (VI) are linked together with one another via terephthalic acid and / or isophthalic acid to form an ester group.

[0056] In formula (4a), p=0, V is C3-alkylene, r=1, Z is C2-alkylene, R 8 and R 9 is methyl, q=1, W is C3-alkylene, m=1, R 5 is hydrogen or C1-C4-alkyl, preferably hydrogen or methyl; R 6 and R 7 is also preferably each independently C1-C4 alkyl, preferably methyl, and o is 10-500.

[0057] Copolycarbonates having monomeric units of formula (4a) and in particular their preparation are also described in WO 2015 / 052106.

[0058] Copolycarbonates having monomeric units of formula (IV) and in particular their preparation are also described in WO 2015 / 052106.

[0059] Examples of aromatic dicarboxylic acids suitable for the preparation of polyester carbonates include orthophthalic acid, terephthalic acid, isophthalic acid, tert-butylisophthalic acid, 3,3'-diphenyldicarboxylic acid, 4,4'-diphenyldicarboxylic acid, 4,4-benzophenonedicarboxylic acid, 3,4'-benzophenonedicarboxylic acid, 4,4'-diphenyletherdicarboxylic acid, 4,4'-diphenylsulfonedicarboxylic acid, 2,2-bis(4-carboxyphenyl)propane, trimethyl-3-phenylindane-4,5'-dicarboxylic acid.

[0060] Among the aromatic dicarboxylic acids, particular preference is given to the use of terephthalic acid and / or isophthalic acid.

[0061] Derivatives of dicarboxylic acids include dicarbonyl dihalides and dialkyl dicarboxylates, especially dicarbonyl dichlorides and dimethyl dicarboxylates.

[0062] The replacement of carbonate groups with aromatic dicarboxylic ester groups is substantially stoichiometric and quantitative, so that the molar ratios of the reactants are also maintained in the final polyestercarbonate. The aromatic dicarboxylic ester groups can be incorporated either randomly or in blocks.

[0063] The composition according to the invention contains at least 68% by weight, preferably at least 75% by weight, particularly preferably at least 80% by weight, of aromatic polycarbonate and is therefore based on aromatic polycarbonate. The aromatic polycarbonate according to component A preferably comprises bisphenol A homopolycarbonate. Particularly preferably, the polycarbonate is bisphenol A homopolycarbonate.

[0064] Component B Component B is a (meth)acrylate copolymer. It will be understood that this may be the only (meth)acrylate copolymer or a mixture of various (meth)acrylate copolymers. Component B does not include polymers that include a polyalkyl (meth)acrylate as part of the graft polymer. The polyalkyl (meth)acrylate is preferably a linear polymer.

[0065] The (meth)acrylate copolymer according to component B preferably has a weight average molecular weight of 5000 g / mol to 30000 g / mol, more preferably 10000 g / mol to 25000 g / mol, as determined by gel permeation chromatography in tetrahydrofuran using PMMA calibration.

[0066] The weight average molecular weight specified is based on all (meth)acrylate copolymers present in the composition according to the invention, ie possibly a mixture of various (meth)acrylate copolymers.

[0067] The (meth)acrylate copolymer comprises aromatic (meth)acrylate units (b1) and also methyl methacrylate units (b2) in a weight ratio (b1 / b2) of (5% to 80% by weight) / (20% to 95% by weight), particularly preferably (5% to 20% by weight) / (80% to 95% by weight), the figures being based on the total weight of the (meth)acrylate copolymer. According to the present invention, "(meth)acrylate" means acrylate or methacrylate.

[0068] The aromatic (meth)acrylate forming unit b1 is a (meth)acrylate having an aromatic group in its ester group. Such (meth)acrylate can be used alone or in a mixture with further aromatic (meth)acrylate. Examples of aromatic (meth)acrylate are phenyl (meth)acrylate and benzyl (meth)acrylate, which are preferred aromatic (meth)acrylates according to the invention. Phenyl (meth)acrylate is particularly preferably used in unit b1, particularly preferably exclusively.

[0069] The unit b2 is formed by methyl methacrylate.

[0070] The proportion of component B in the composition according to the present invention is from 4% by weight to 25% by weight, preferably from 5% by weight to 22% by weight, more preferably from 5% by weight to 20% by weight, even more preferably from 15% by weight to 15% by weight, and particularly preferably from 5% by weight to 10% by weight, based on the entire composition.

[0071] Component C Component C of the composition according to the invention is a phosphorus-containing flame retardant, which may be a single phosphorus-containing flame retardant or a mixture of different phosphorus-containing flame retardants.

[0072] Suitable phosphorus-containing flame retardants are cyclic phosphazenes, phosphorus compounds of formula (10), and mixtures thereof: [ka] During the ceremony, R 1 , R 2 , R 3 , and R 4 are independently a C1-C8-alkyl radical, which in each case is optionally halogenated, in each case branched or unbranched, and / or a C5-C6-cycloalkyl radical, a C6-C 20 -aryl radical, or C7-C 12- aralkyl radicals, which in each case are optionally substituted by branched or unbranched alkyl and / or halogen, preferably chlorine and / or bromine, n is independently 0 or 1; q is a value between 0 and 30; X is a monocyclic or polycyclic aromatic radical having 6 to 30 carbon atoms, or a straight or branched chain aliphatic radical having 2 to 30 carbon atoms, each of which can be substituted or unsubstituted and bridged or non-bridged.

[0073] Preferably, R 1 , R 2 , R 3 , and R 4 is independently branched or unbranched C1-C4-alkyl, phenyl, naphthyl, or C1-C4-alkyl-substituted phenyl. 1 Group, R 2 Group, R 3 Groups and / or R 4 If they are radicals, these in turn can be substituted by halogens and / or alkyl groups, preferably chlorine, bromine and / or branched or unbranched C1-C4-alkyl. Particularly suitable aryl radicals are those corresponding to cresyl, phenyl, xylenyl, propylphenyl or butylphenyl, as well as their brominated and chlorinated derivatives.

[0074] X in formula (10) is preferably derived from a dihydroxyaryl compound.

[0075] X in formula (10) is particularly preferably the following: [ka] or their chlorinated and / or brominated derivatives. X (together with the adjacent oxygen atom) is preferably derived from hydroquinone, bisphenol A or diphenylphenol. It is likewise suitable that X is derived from resorcinol. Particularly preferably, X is derived from bisphenol A. n in formula (10) is preferably equal to 1. q is preferably 0 to 20, particularly preferably 0 to 10, and in the case of mixtures has an average value of 0.8 to 5.0, preferably 1.0 to 3.0, further preferably 1.05 to 2.00, particularly preferably 1.08 to 1.60.

[0076] The phosphorus compound of the general formula (10) is preferably a compound of the formula (11), [ka] During the ceremony, R 1 , R 2 , R 3 , and R 4 are each independently a linear or branched C1-C8 alkyl radical and / or optionally a linear or branched alkyl substituted C5-C6 cycloalkyl radical, C6-C 10 -aryl radical, or C7-C 12 -aralkyl radical, n is independently 0 or 1; q is independently 0, 1, 2, 3, or 4; N is a number between 1 and 30, R 5 and R 6 are independently a linear or branched C1-C4-alkyl radical, preferably a methyl radical, Y is a linear or branched C1-C7 alkylidene, linear or branched C1-C7 alkylene radical, C5-C 12 -Cycloalkylene radical, C5-C 12 - a cycloalkylidene radical, -O-, -S-, -SO-, SO2, or -CO-.

[0077] Phosphorus compounds of formula (10) include, in particular, tributyl phosphate, triphenyl phosphate, tricresyl phosphate, cresyl diphenyl phosphate, octyl diphenyl phosphate, 2-ethyl cresyl diphenyl phosphate, tri(isopropylphenyl) phosphate, resorcinol bridged oligophosphates, and bisphenol A bridged oligophosphates. The use of oligomeric phosphates of formula (10) derived from bisphenol A is particularly preferred.

[0078] Further preference is given to the use of mixtures of the same structure but different chain lengths, in which case the q value specified is the average of the q values, determined by determining the composition (molecular weight distribution) of the mixture of phosphorus compounds by high pressure liquid chromatography (HPLC) in a mixture of acetonitrile and water (50:50) at 40°C and using this to calculate the average value of q.

[0079] Particularly preferably, bisphenol A-based oligophosphates according to formula (12) (bisphenol A bis(diphenyl phosphate)) with q=1 to 20, in particular q=1.0 to 1.2, are present in the composition according to the invention. [ka]

[0080] Phosphorus compounds of this type are known (see, for example, EP-A-0 363 608, EP-A-0 640 655) or can be prepared in an analogous manner by known methods (see, for example, Ullmanns Enzyklopaedie der technischen Chemie [Ullmann's Encyclopedia of Industrial Chemistry], vol. 18, p. 301 ff. 1979; Houben-Weyl, Methoden der organischen Chemie [Methods of Organic Chemistry], vol. 12 / 1, p. 43; Beilstein vol. 6, p. 177).

[0081] When an organic phosphate ester is used as the phosphorus-containing flame retardant, it is preferably used in an amount of 2% by weight to 8% by weight.

[0082] As preferred as the phosphorus compounds according to formula (10), it is also possible to use as component C cyclic phosphazenes according to formula (13), [ka] During the ceremony, R is in each case the same or different, is an amine radical, in each case an optionally halogenated, preferably fluorohalogenated, more preferably monohalogenated, C1-C8-alkyl radical, preferably a methyl, ethyl, propyl or butyl radical, a C1-C8 alkoxy radical, preferably a methoxy, ethoxy, propoxy or butoxy radical, in each case optionally alkyl-substituted, preferably C1-C4-alkyl-substituted and / or halogen-substituted, preferably chlorine- and / or bromine-substituted, C5-C6-cycloalkyl radicals, In each case, optionally alkyl-substituted, preferably C1-C4-alkyl-substituted, and / or halogen-substituted, preferably chlorine, bromine, and / or hydroxy-substituted, C6-C 20 an aryloxy radical, preferably a phenoxy radical, a naphthyloxy radical, In each case, optionally alkyl-substituted, preferably C1-C4-alkyl-substituted, and / or halogen-substituted, preferably chlorine- and / or bromine-substituted, C7-C 12 - an aralkyl radical, preferably a phenyl-C1-C4-alkyl radical, or a halogen radical, preferably chlorine or fluorine, or is the OH radical, k is a natural number of 1 to 10, preferably 1 to 8, particularly preferably 1 to 5, and especially preferably 1.

[0083] Particularly preferably used according to the invention are commercially available phosphazenes, which are typically ring mixtures of different ring sizes.

[0084] Further preference is given to the following, either individually or in mixtures: propoxyphosphazenes, phenoxyphosphazenes, methylphenoxyphosphazenes, aminophosphazenes, fluoroalkylphosphazenes, and also phosphazenes having the following structure: [ka]

[0085] In compounds 13a-13f shown above, k=1, 2, or 3.

[0086] Preferably, the proportion of phosphorus halogen substituted phosphazenes, for example those consisting of incompletely reacted starting materials, is less than 1000 ppm, more preferably less than 500 ppm.

[0087] The phosphazenes can be used alone or in mixtures. The radicals R can always be the same or two or more radicals in the formula can be different. The radicals R of the phosphazenes are preferably identical.

[0088] In one embodiment, only phosphazenes having the same R are used.

[0089] Preferably, the proportion of tetramers (k=2) is 2 mol % to 50 mol %, more preferably 5 mol % to 40 mol %, even more preferably 10 mol % to 30 mol %, particularly preferably 10 mol % to 22 mol %, based on component C.

[0090] Preferably, the proportion of higher oligomeric phosphazenes (k=3, 4, 5, 6, and 7) is from 0 mol% to 30 mol%, more preferably from 2.5 mol% to 25 mol%, even more preferably from 5 mol% to 20 mol%, and particularly preferably from 6 mol% to 15 mol%, based on component C.

[0091] Preferably, the proportion of oligomers with k≧8 is, based on component C, from 0 mol % to 2.0 mol %, preferably from 0.10 mol % to 1.00 mol %.

[0092] More preferably, the phosphazene of component C satisfies all three above conditions with respect to the proportion of oligomers.

[0093] Particularly preferably, phenoxyphosphazenes (all R=phenoxy, formula 13g) are present as component C, either alone or together with further phosphazenes according to formula (13) as component C, the proportion of oligomers with k=1 (hexaphenoxyphosphazenes) being 50 mol % to 98 mol %, particularly preferably 60% to 72% by weight, based on the amount of phenoxyphosphazene. If phenoxyphosphazenes are used, the proportion of oligomers with k=2 is especially preferably 15% to 22% by weight and those with k≧3 being 10% to 13% by weight. [ka]

[0094] Alternatively, component C particularly preferably comprises a phenoxyphosphazene having, based on component C, a proportion of trimers (k=1) of 70 mol% to 85 mol%, a proportion of tetramers (k=2) of 10 mol% to 20 mol%, a proportion of higher oligomeric phosphazenes (k=3, 4, 5, 6, and 7) of 3 mol% to 8 mol%, and 0.1 mol% to 1 mol% of phosphazene oligomers with k≧8. Such a phenoxyphosphazene is particularly preferred.

[0095] In an alternative preferred embodiment, n is defined as the arithmetic mean of k, where n is in the range of 1.10 to 1.75, preferably 1.15 to 1.50, more preferably 1.20 to 1.45, and especially preferably 1.20 to 1.40 (including the range limits).

number

[0096] Phosphazenes and their preparation are described, for example, in EP-A-728811, DE-A-1961668 and WO-A-97 / 40092.

[0097] The oligomer composition in each blend sample was determined after synthesis as follows: 31 Detection and quantification are possible by P NMR (chemical shifts; trimer δ: 6.5 ppm to 10.0 ppm; tetramer δ: -10 ppm to -13.5 ppm; higher oligomers δ: -16.5 ppm to -25.0 ppm).

[0098] When the phosphorus-containing flame retardant is a phosphazene, it is preferably used in an amount of from 2 to 8% by weight, more preferably from 4 to 8% by weight.

[0099] Particularly preferably, component C comprises a bisphenol A-based oligophosphate ester according to formula (12) and / or a cyclic phosphazene according to formula (13), and most preferably component C is a bisphenol A-based oligophosphate ester according to formula (12) and / or a cyclic phosphazene according to formula (13).

[0100] The proportion of phosphorus-containing flame retardant in the composition according to the invention is 2% to 10% by weight, preferably 2% to 8% by weight, particularly preferably up to 6% by weight, especially preferably up to 5% by weight, very particularly preferably up to 4% by weight, based on the entire composition. The Vicat temperature decreases significantly with increasing proportion of phosphorus-containing flame retardant.

[0101] Component D The composition according to the present invention contains a fluorine-containing anti-drip agent comprising polytetrafluoroethylene as component D, which may be a mixture of two or more anti-drip agents. The total amount of the anti-drip agent (anti-drip agent) is 0.25% to 2% by weight, preferably 0.4% to 1% by weight, particularly preferably 0.5% to 1.0% by weight of at least one anti-drip agent.

[0102] The fluorinated polyolefins used preferentially as anti-drip agents are of high molecular weight, have a glass transition temperature above -30°C, generally above 100°C, and a fluorine content preferably between 65% and 76% by weight, in particular between 70% and 76% by weight. Suitable fluorinated polyolefins are in all cases polytetrafluoroethylene, polyvinylidene fluoride, tetrafluoroethylene / hexafluoropropylene copolymers and ethylene / tetrafluoroethylene copolymers. Fluorinated polyolefins are known ("Vinyl and Related Polymers" by Schildknecht, John Wiley & Sons, Inc., New York, 1962, pages 484-494; "Fluoropolymers" by Wall, Wiley-Interscience, John Wiley & Sons, Inc., New York, volume 13, 1970, pages 623-654; "Modern Plastics Encyclopedia", 1970-1971, volume 47, No. 10 A, October 1970, McGraw-Hill, Inc., New York, pages 134 and 774; "Modern Plastics Encyclopedia", 1975-1976, October 1975, volume 52, No. 10 A, McGraw-Hill, Inc., New York, pages 27, 28 and (See U.S. Pat. Nos. 3,671,487, 3,723,373, and 3,838,092.) These can be prepared by known methods, for example, in an aqueous medium using a free radical forming catalyst (e.g., sodium peroxodisulfate, potassium peroxodisulfate, or ammonium peroxodisulfate, etc.) at a pressure of 7 kg / cm. 2 ~71kg / cm 2 and polymerizing tetrafluoroethylene at a temperature between 0° C. and 200° C., preferably between 20° C. and 100° C. Further details can be obtained, for example, in US Pat. No. 2,393,967.

[0103] Depending on the application, the density of the fluorinated polyolefins is specified according to ISO 1183-1 (2019-09) to be 1.2 g / cm 3 ~2.3g / cm 3 , preferably 2.0 g / cm 3 ~2.3g / cm 3 The average particle size can be between 0.05 μm and 1000 μm as determined by optical microscopy or white light interferometry.

[0104] Suitable tetrafluoroethylene polymer powders are commercially available, for example, from DuPont under the trade name Teflon™.

[0105] Thus, the use of polytetrafluoroethylene (PTFE) is particularly preferred, but the fluorine-containing anti-drip agent is also used in the form of a PTFE-containing composition. When a PTFE-containing composition is used, the minimum amount of PTFE present in the entire composition is preferably at least 0.15% by weight, particularly preferably at least 0.25% by weight. PTFE-containing compositions include Hostaflon™ TF2021 or PTFE blends, such as Blendex™ B449 from Chemtura (about 50% by weight PTFE and about 50% by weight SAN (derived from 80% by weight styrene and 20% by weight acrylonitrile)). Particular preference is given to the use of PTFE or a PTFE / SAN blend as the fluorine-containing anti-drip agent, and particularly preferably the fluorine-containing anti-drip agent is PTFE or PTFE / SAN.

[0106] Component E The polycarbonate compositions according to the present invention may contain one or more additional additives different from Component B, Component C, and Component D, which, when present, are collectively referred to as "Component E."

[0107] Other usual additives ("additional additives") are optionally present (0 wt.%), preferably up to 12 wt.%, more preferably up to 5 wt.%, even more preferably up to 3 wt.%, in particular 0.1 wt.% to 3 wt.%, particularly preferably 0.2 wt.% to 1 wt.%, especially preferably 0.5 wt.% to 1.0 wt.%, these weight percentages being based on the total weight of the composition. The group of additional additives does not include any phosphorus-containing flame retardants according to component C. In particular, the group of additional additives does not include any fluorine-containing anti-drip agents, since these have already been described in component D.

[0108] Such additional additives are typically added to polycarbonates, such as heat stabilizers, antioxidants, release agents, UV absorbers, IR absorbers, impact modifiers, antistatic agents, optical brighteners, light scattering agents, hydrolysis stabilizers, transesterification stabilizers, (organic) dyes, (organic / inorganic) pigments (including carbon black and titanium dioxide), compatibilizers, and / or laser marking additives, in amounts typical of compositions based on polycarbonates. Such additives are described, for example, in EP-A-0839623, WO-A-96 / 15102, EP-A-0500496, or in "Plastics Additives Handbook", Hans Zweifel, 5th Edition 2000, Hanser Verlag, Munich. Such additives can be added individually or else as mixtures.

[0109] If additional additives are eventually present, more preferably the additional additives are one or more selected from the group consisting of heat stabilizers, antioxidants, mold release agents, organic dyes, organic pigments, inorganic pigments.

[0110] Further additives present are particularly preferably at least one heat stabilizer, antioxidant and / or mold release agent.

[0111] It will be understood that such additives may only be added in such amounts if they do not significantly negatively affect the effect of the present invention, which combines high CTI with good flame retardancy, and preferably also do not reduce the Vicat temperature, as determined according to ISO 306:2014-3, VST method B, to below 105°C, more preferably below 108°C.

[0112] The composition according to the invention may indeed contain, in addition to component C, further flame retardants, but does not include those selected from the group of alkali metal, alkaline earth metal or ammonium salts of aliphatic or aromatic sulfonic acid, sulfonamide or sulfonimide derivatives, and combinations thereof, "derivatives" being taken to mean compounds having a molecular structure in which, instead of a hydrogen atom or a functional group, a different atom or a different atomic group has been present, or in which one or more atoms / atoms have been removed, so that the parent compound is still recognizable.

[0113] Such flame retardants not present in the composition according to the invention are in particular one or more compounds selected from the group consisting of sodium or potassium perfluorobutane sulfate, sodium or potassium perfluoromethanesulfonate, sodium or potassium perfluorooctane sulfate, sodium or potassium 2,5-dichlorobenzenesulfate, sodium or potassium 2,4,5-trichlorobenzenesulfonate, sodium or potassium diphenylsulfonesulfonate, sodium or potassium 2-formylbenzenesulfonate, sodium or potassium (N-benzenesulfonyl)benzenesulfonamide or mixtures thereof, among which particular preference is given to sodium or potassium perfluorobutanesulfate, sodium or potassium perfluorooctane sulfate, sodium or potassium diphenylsulfonesulfonate or mixtures thereof, in particular potassium perfluoro-1-butanesulfonate (which is commercially available, inter alia, as Bayowet® C4 from Lanxess, Leverkusen, Germany).

[0114] Additives which are particularly preferably present are release agents, more preferably release agents based on fatty acid esters, even more preferably release agents based on stearic acid esters, particularly preferably release agents based on pentaerythritol. Particular preference is given to the use of pentaerythritol tetrastearate (PETS) and / or glycerol monostearate (GMS). If one or more release agents are used, their amount is preferably up to 1.0% by weight (inclusive), more preferably 0.01% to 0.7% by weight, particularly preferably 0.2% to 0.60% by weight, in each case based on the total composition.

[0115] An additive which is also particularly preferably present is a heat stabilizer, the amount of which is preferably up to 0.20% by weight, more preferably from 0.01% to 0.15% by weight, even more preferably from 0.01% to 0.1% by weight, and particularly preferably from 0.025% to 0.09% by weight, based on the total composition.

[0116] Suitable heat stabilizers are especially phosphorus-based stabilizers selected from the group of phosphates, phosphites, phosphonites, phosphines, and mixtures thereof.Examples include triphenyl phosphite, alkyl diphenyl phosphite, dialkyl phenyl phosphite, tris(nonylphenyl) phosphite, trilauryl phosphite, trioctadecyl phosphite, distearyl pentaerythritol diphosphite, tris(2,4-di-tert-butylphenyl) phosphite (Irgafos® 168), diisodecyl pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite, bis(2,4-dicumylphenyl) pentaerythritol diphosphite (Do verphos(trademark) S-9228), bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, diisodecyloxypentaerythritol diphosphite, bis(2,4-di-tert-butyl-6-methylphenyl)pentaerythritol diphosphite, bis(2,4,6-tris(tert-butylphenyl)pentaerythritol diphosphite, tristearyl sorbitol triphosphite, tetrakis(2,4-di-tert-butylphenyl)-4,4'-biphenylene diphosphonite, 6-isooctyl peroxy-2,4,8,10-tetra-tert-butyl-12H-dibenzo[d,g]-1,3,2-dioxaphosphocin, bis(2,4-di-tert-butyl-6-methylphenyl)methyl phosphite, bis(2,4-di-tert-butyl-6-methylphenyl)ethyl phosphite, 6-fluoro-2,4,8,10-tetra-tert-butyl-12-methyldibenzo[d,g]-1,3,2-dioxaphosphocin, 2,2',2''-nitrilo[triethyltris(3,3',5,5'-tetra-tert-butyl-1,1'-biphenyl 2-ethylhexyl (3,3',5,5'-tetra-tert-butyl-1,1'-biphenyl-2,2'-diyl) phosphite, 5-butyl-5-ethyl-2-(2,4,6-tri-tert-butylphenoxy)-1,3,2-dioxaphosphiran, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, triphenylphosphine (TPP), trialkylphenylphosphine, bisdiphenylphosphinoethane, or trinaphthylphosphine.These can be used alone or in mixtures, for example Irganox® B900 (a mixture of Irgafos® 168 and Irganox® 1076 (antioxidant) in a ratio of 4:1) or a mixture of Doverphos® S-9228 with Irganox® B900 or Irganox® 1076. Particularly preferably, triphenylphosphine (TPP), Irgafos® 168, or tris(nonylphenyl)phosphite, or mixtures thereof, are used.

[0117] It is also possible to use phenolic antioxidants, such as alkylated monophenols, alkylated thioalkylphenols, hydroquinones and alkylated hydroquinones.Particular preference is given to using Irganox® 1010 (pentaerythritol 3-(4-hydroxy-3,5-di-tert-butylphenyl)propionate; CAS: 6683-19-8) and Irganox® 1076 (octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), preferably in an amount of 0.01% to 0.5% by weight.

[0118] It is also possible to add sulfonates or alkyl phosphates, such as mono-, di-, and / or trihexyl phosphate, triisooctyl phosphate, and / or trinonyl phosphate, as transesterification inhibitors. The alkyl phosphate used is preferably triisooctyl phosphate (tris-2-ethylhexyl phosphate). It is also possible to use mixtures of various mono-, di-, and / or trialkyl phosphates. Triisooctyl phosphate is preferably used in an amount of 0.003% to 0.05% by weight, more preferably 0.005% to 0.04% by weight, particularly preferably 0.01% to 0.03% by weight, based on the total composition.

[0119] Examples of impact modifiers are: core-shell polymers, such as ABS or MBS; olefin-acrylate copolymers, such as the Elvaloy™ variety from DuPont or the Paraloid™ variety from Dow; silicone acrylate rubbers, such as the Metablen™ variety from Mitsubishi Rayon Co., Ltd. The composition according to the present invention already has an exceptional property profile without additional impact modifiers. Therefore, the composition according to the present invention preferably does not contain impact modifiers.

[0120] Particularly preferably, no fillers are present in the composition according to the invention.

[0121] Particularly preferred compositions according to the invention are A) at least 68% by weight of an aromatic polycarbonate; B) 4% by weight to 25% by weight of a (meth)acrylate copolymer containing aromatic (meth)acrylate units b1 and methyl methacrylate units b2 in a weight ratio b1 / b2 of (5% by weight to 20% by weight) / (80% by weight to 95% by weight) based on the total weight of the (meth)acrylate copolymer; C) 2% by weight to 10% by weight of a phosphorus-containing flame retardant; D) 0.25% by weight to 2% by weight of a fluorine-containing drip prevention agent containing polytetrafluoroethylene; E) one or more additional additives selected from the group consisting of one or more mold release agents, heat stabilizers, antioxidants, dyes, pigments, ultraviolet absorbers, infrared absorbers, impact modifiers, antistatic agents, optical brighteners, hydrolysis stabilizers, ester interchange stabilizers, compatibilizers, laser marking additives, and mixtures thereof; It consists only of The weight percent figures are based on the total composition. The ratio of the amount of (meth)acrylate copolymer in weight percent to the amount of phosphorus-containing flame retardant in weight percent is less than or equal to 2.5, and the ratio of the amount of (meth)acrylate copolymer in weight percent to the amount of polytetrafluoroethylene in weight percent is less than or equal to 20.

[0122] Particularly preferred compositions according to the invention are A) at least 75% by weight of an aromatic polycarbonate; B) 5% by weight to 20% by weight of a (meth)acrylate copolymer containing aromatic (meth)acrylate units b1 and methyl methacrylate units b2 in a weight ratio b1 / b2 of (5% by weight to 20% by weight) / (80% by weight to 95% by weight) based on the total weight of the (meth)acrylate copolymer; C) 2% by weight to 8% by weight of a phosphorus-containing flame retardant; D) 0.25% by weight to 2% by weight of a fluorine-containing drip prevention agent containing polytetrafluoroethylene; E) 0% to 5% by weight of one or more additional additives selected from the group consisting of one or more release agents, heat stabilizers, antioxidants, dyes, pigments, ultraviolet absorbers, infrared absorbers, impact modifiers, optical brighteners, hydrolysis stabilizers, ester exchange stabilizers, compatibilizers, laser marking additives, and mixtures thereof; It consists only of The weight percent figures are based on the total composition. The ratio of the amount of (meth)acrylate copolymer in weight percent to the amount of phosphorus-containing flame retardant in weight percent is less than or equal to 2.5, and the ratio of the amount of (meth)acrylate copolymer in weight percent to the amount of polytetrafluoroethylene in weight percent is less than or equal to 20.

[0123] Particularly preferred compositions according to the invention are A) at least 75% by weight of an aromatic polycarbonate; B) 5% to 20% by weight of a (meth)acrylate copolymer, containing aromatic (meth)acrylate units b1 in an amount of 5% to 20% by weight and methyl methacrylate units b2 in an amount of 80% to 95% by weight, based on the total weight of the (meth)acrylate copolymer; C) 2% to 8% by weight of a phosphorus-containing flame retardant; D) 0.25% by weight to 2% by weight of a fluorine-containing anti-drip agent containing polytetrafluoroethylene; E) 0% to 5% by weight of one or more additional additives selected from the group consisting of one or more mold release agents, heat stabilizers, antioxidants, dyes, pigments, and mixtures thereof; It consists only of The weight percent figures are based on the total composition. The ratio of the amount of (meth)acrylate copolymer in weight percent to the amount of phosphorus-containing flame retardant in weight percent is less than or equal to 2.5, and the ratio of the amount of (meth)acrylate copolymer in weight percent to the amount of polytetrafluoroethylene in weight percent is less than or equal to 20.

[0124] In this case, the phosphorus-containing flame retardants present are preferably organic phosphates, in particular those of formula (12): [ka] (In the formula, q=1 to 20, particularly 1.0 to 1.2) Or, Phosphazenes of formula (13g): [ka] (wherein k=1, 2, or 3, including mixtures thereof) It will be understood that this is preferably a mixture of various oligomers of this formula, since such mixtures are typically commercially available. Particular preference is given to the use of phosphorus-containing flame retardants of one of the formulae (12) or (13g) as defined above.

[0125] The polymer composition according to the invention, which contains the components A, B, C, D and, optionally, E in admixture, can be prepared using a powder premix. It is also possible to use a plurality of pellet materials or premixes of pellet materials and powders with the additives according to the invention. It is also possible to use a premix formed from a solution of the component mixture in a suitable solvent, optionally followed by homogenization of the solution and subsequent removal of the solvent. In particular, the additives, designated as component E of the composition according to the invention, can also be introduced by known methods or in the form of a masterbatch. The use of masterbatches is particularly suitable for the introduction of the additives and further components, and masterbatches based on the respective polymer matrix are particularly used.

[0126] The composition according to the invention can be extruded, for example. After extrusion, the extrudate can be cooled and crushed. The premix can also be mixed together in the melt in the plasticizing unit of an injection molding machine. In this case, the melt is directly converted into a molded article in a subsequent step.

[0127] The compositions according to the invention are preferably used for the manufacture of moldings for components of the EE sector, in particular for high voltage switches, inverters, relays, electronic connectors, electrical connectors, circuit breakers, components for photovoltaic applications, electric motors, heat sinks, chargers and charging plugs for electric vehicles, electrical junction boxes, smart meter housings, miniature circuit breakers, busbars. The invention therefore also provides moldings which are part of the corresponding components. Here "part of" means that this can be a complex product, an individual element of a group of components, but also the whole element, as is the case for example with "electronic connectors".

[0128] Moldings in the sense of the present invention are also insulating layers made of the compositions according to the present invention. Such layers can be provided, for example, on inverters as layers that protect against external influences. For inverters, standard insulating materials have a CTI of 600V. The compositions according to the present invention can also be used as insulating layers for other electrical components, for example transistors. The insulating layer provides a reliable separation, for example, between the transistor and the metal heat sink.

[0129] The components are preferably designed for a working voltage of at least 400 V. However, they can also be designed for typical European household working voltages of 230 V±23 V, although a reduction in the distance of the conductors can be achieved here. The mouldings are preferably used such that the mouldings themselves have a comparative tracking index, specified as above, of at least 600 V.

[0130] The invention therefore also provides moldings which consist exclusively of the composition according to the invention or which contain areas made of the composition according to the invention, as well as corresponding parts which contain elements or moldings which consist exclusively of the composition according to the invention or which contain areas made exclusively of the composition according to the invention.

[0131] The high comparative tracking index of the polycarbonate composition according to the invention makes it possible to use this polycarbonate material to reduce the distance between two conductors in a component than was previously possible using polycarbonate.

[0132] Accordingly, the present invention also provides an EE component, comprising a first conductor and a second conductor at a first distance d1 and a second distance d2 relative to each other, These electrical conductors are connected via an element made of a thermoplastic composition according to the invention, which is in direct contact with the first electrical conductor and the second electrical conductor, distance d1 is the shortest distance between the first and second electrical conductors along a surface of the element made of the thermoplastic composition; Distance d2 is the shortest distance between the first conductor and the second conductor through air; d2 is selected so as to prevent sparks through the air at each operating voltage; d1 is as follows, at the working voltage U listed below: d1i(0V≦U≦250V):1.3mm~<2.5mm d1ii(250V <U≦500V)=2.5mm~<5.0mm d1iii(500V <U≦1000V)=5.0mm~<10.0mm。

[0133] Such small lower limits on the distance between conductors are achievable only with materials having a CTI of at least 600 V. Even the upper range of these small distance ranges can only be achieved if the materials used have a CTI of at least 400 V.

[0134] For this reason, the distance ranges detailed below are only achievable at the following specified working voltages if the material has a CTI of at least 400V: d1i(0V≦U≦250V):1.8mm~<2.5mm d1ii(250V <U≦500V)=3.6mm~<5.0mm d1iii(500V <U≦1000V)=7.1mm~<10.0mm。

[0135] Particularly preferably, when a material having a CTI of 600V is used as described as part of the present invention, d1 at the stated working voltage is as follows: d1i(0V≦U≦250V):1.3mm~<1.8mm, d1ii(250V <U≦500V)=2.5mm~<3.6mm、 d1iii(500V <U≦1000V)=5.0mm~<7.1mm、 , which are distances that are not achievable even with materials with a CTI of 400V or 450V, and require a CTI of 600V.

[0136] Because of this, it is possible to achieve EE components using polycarbonate materials between two conductors with smaller distances than previously thought possible.

[0137] The selection of d2 is within the ability of one skilled in the art. Preferably, d2 is at least 1.2 mm.

[0138] By "element made of a thermoplastic composition according to the invention" is meant herein the presence of an element which consists exclusively of a thermoplastic composition according to the invention.

[0139] It is known that the degree of contamination affects the electrical conductivity. The mentioned distances d1 and d2 are practical for example in components that, due to structural shielding, comply with the IP6K9K degree of protection according to ISO 20653:2013-02.

[0140] Thermoplastic compositions which are suitable according to the invention belong to insulating material group I (600 V≦CTI) as classified according to DIN EN 60664-1.

[0141] Due to the high comparative tracking index of the materials used, the EE components according to the invention are preferably used in EE assemblies designed for working voltages of at least 400 V, possibly even 600 V. The invention therefore also provides a corresponding EE assembly.

[0142] Various embodiments of the present invention are described below:

[0143] 1. A thermoplastic composition comprising: A) at least 68% by weight of an aromatic polycarbonate; B) 4% by weight to 25% by weight of a (meth)acrylate copolymer containing aromatic (meth)acrylate units b1 and methyl methacrylate units b2 in a weight ratio b1 / b2 of (5% by weight to 20% by weight) / (80% by weight to 95% by weight) based on the total weight of the (meth)acrylate copolymer; C) 2% by weight to 10% by weight of a phosphorus-containing flame retardant; D) 0.25% by weight to 2% by weight of a fluorine-containing drip prevention agent containing polytetrafluoroethylene; E) one or more additional additives selected from the group consisting of one or more mold release agents, heat stabilizers, antioxidants, dyes, pigments, ultraviolet absorbers, infrared absorbers, impact modifiers, antistatic agents, optical brighteners, hydrolysis stabilizers, ester interchange stabilizers, compatibilizers, laser marking additives, and mixtures thereof; Contains The weight percent figures are based on the total composition. the ratio of the amount of (meth)acrylate copolymer in weight percent to the amount of phosphorus-containing flame retardant in weight percent is less than or equal to 2.5, and the ratio of the amount of (meth)acrylate copolymer in weight percent to the amount of polytetrafluoroethylene in weight percent is less than or equal to 20; The thermoplastic composition does not contain a flame retardant selected from the group consisting of alkali metal, alkaline earth metal and ammonium salts of aliphatic or aromatic sulfonic acid, sulfonamide and sulfonimide derivatives. Thermoplastic composition.

[0144] 2. The thermoplastic composition according to embodiment 1, wherein the ratio of the amount of (meth)acrylate copolymer in wt.% to the amount of polytetrafluoroethylene in wt.% is less than or equal to 10.

[0145] 3. The thermoplastic composition according to embodiment 1 or 2, wherein the phosphorus-containing flame retardant is an organophosphate ester, a phosphazene, or a mixture thereof.

[0146] 4. The phosphorus-containing flame retardant is an organic phosphate ester of the formula (11), [ka] During the ceremony, R 1 , R 2 , R 3 , and R 4are each independently a linear or branched C1-C8 alkyl radical and / or an optionally linear or branched alkyl substituted C5-C6 cycloalkyl radical, a C6-C 10 -aryl radical, or C7-C 12 -aralkyl radical, n is independently 0 or 1; q is independently 0, 1, 2, 3, or 4; N is a number between 1 and 30, R 5 and R 6 are independently a linear or branched C1-C4-alkyl radical, preferably a methyl radical, Y is a linear or branched C1-C7 alkylidene, linear or branched C1-C7 alkylene radical, C5-C 12 -Cycloalkylene radical, C5-C 12 - a cycloalkylidene radical, -O-, -S-, -SO-, SO2, or -CO-; A thermoplastic composition according to any of the previous embodiments.

[0147] 5. As a phosphorus-containing flame retardant, there is a phosphazene of the formula (13g): [ka] wherein k=1, 2, or 3, including mixtures thereof; A thermoplastic composition according to any of the previous embodiments.

[0148] 6. A thermoplastic composition according to any of the previous embodiments, wherein the composition contains 5% to 20% by weight of the (meth)acrylate copolymer.

[0149] 7. A thermoplastic composition according to any of the previous embodiments, wherein the composition contains 0.3 wt.% to 1.0 wt.% of a mold release agent.

[0150] 8. A thermoplastic composition according to any of the previous embodiments, wherein the composition contains a total of 0.02 wt.% to 0.15 wt.% of a heat stabilizer and / or antioxidant.

[0151] 9. The thermoplastic composition according to any of the previous embodiments, wherein the amount of phosphorus-containing flame retardant is from 2% to 8% by weight.

[0152] 10. A thermoplastic composition according to any of the previous embodiments, wherein component B has a weight average molecular weight, as determined by gel permeation chromatography in tetrahydrofuran using PMMA calibration, of 5000 g / mol to 300000 g / mol.

[0153] 11. A thermoplastic composition according to any of the previous embodiments, wherein component B has a weight average molecular weight of 10,000 g / mol to 25,000 g / mol, as determined by gel permeation chromatography in tetrahydrofuran using PMMA calibration.

[0154] 12. The thermoplastic composition according to any of the previous embodiments, wherein the aromatic (meth)acrylate is phenyl (meth)acrylate and / or benzyl (meth)acrylate.

[0155] 13. A thermoplastic composition according to any of the previous embodiments, wherein the thermoplastic composition, in addition to Component A, Component B, Component C, and Component D, also contains, solely as Component E, one or more heat stabilizers, antioxidants, mold release agents, dyes, pigments, and mixtures thereof.

[0156] 14. A molding consisting solely of a thermoplastic composition according to any of the previous embodiments or comprising a region made of a thermoplastic composition according to any of the previous embodiments.

[0157] 15. The molding according to embodiment 14, wherein the molding is part of a high voltage switch, an inverter, a relay, an electronic connector, an electrical connector, a circuit breaker, a photovoltaic power system, an electric motor, a heat sink, an electric vehicle charger, an electrical junction box, a smart meter housing, a miniature circuit breaker, or a busbar.

[0158] 16. The molding according to embodiment 14 or embodiment 15, wherein the molding is part of an EE part designed for a working voltage of at least 375 V.

[0159] 17. The molding according to any of embodiments 14-16, wherein the molding is part of an EE part designed for a working voltage of at least 400 V.

[0160] 18. The molding according to any of embodiments 14-17, wherein the molding is part of an EE part designed for a working voltage of at least 500 V.

[0161] 19. The molding according to any of embodiments 14-18, wherein the molding is part of an EE part designed for a working voltage of at least 600 V.

[0162] 20. 1. An EE component comprising a first conductor and a second conductor at a first distance d1 and a second distance d2 relative to each other, These electrical conductors are connected via an element made of a thermoplastic composition according to any one of the first to thirteenth embodiments, the element being in direct contact with the first and second electrical conductors; distance d1 is the shortest distance between the first and second electrical conductors along a surface of the element made of the thermoplastic composition; Distance d2 is the shortest distance between the first conductor and the second conductor through air; d2 is selected so as to prevent sparks through the air at each operating voltage; d1 is as follows, at the working voltage U listed below: d1i(0V≦U≦250V):1.3mm~<2.5mm d1ii(250V <U≦500V)=2.5mm~<5.0mm d1iii(500V <U≦1000V)=5.0mm~<10.0mm。

[0163] 21.d1 at the working voltage U listed below: d1i(0V≦U≦250V):1.3mm~<1.8mm, d1ii(250V <U≦500V)=2.5mm~<3.6mm、 d1iii(500V <U≦1000V)=5.0mm~<7.1mm、 An EE part according to embodiment 20.

[0164] 22. An EE part according to any of embodiments 20 and 21, wherein d2 is 1.2 mm or greater.

[0165] 23. An EE part according to any of embodiments 20 to 22, having an IP6K9K degree of protection according to ISO 20653:2013-02.

[0166] 24. An EE component according to any of embodiments 20 to 23, designed for a working voltage of at least 400V, preferably at least 500V, particularly preferably at least 600V.

[0167] 25. An EE part according to any of embodiments 20-24, in which the element made of the thermoplastic composition according to any of embodiments 1-13 is a molding according to any of embodiments 14-19.

[0168] 26. The EE part according to any of embodiments 20 to 25, which is part of a high voltage switch, an inverter, a relay, an electronic connector, an electrical connector, a circuit breaker, a photovoltaic power system, an electric motor, a heat sink, an electric vehicle charger or charging plug, an electrical junction box, a smart meter housing, a miniature circuit breaker, or a busbar.

[0169] 27. Use of a combination of 4% to 25% by weight of a (meth)acrylate copolymer containing aromatic (meth)acrylate units b1 and methyl methacrylate units b2 in a weight ratio b1 / b2 of (5% to 20% by weight) / (80% to 95% by weight) based on the total weight of the (meth)acrylate copolymer, 0.25% to 2% by weight of a fluorine-containing anti-drip agent containing polytetrafluoroethylene, and 2% to 10% by weight, preferably 2% to 8% by weight of a phosphorus-containing flame retardant, in a thermoplastic polycarbonate-based composition to achieve a CTI of 600V at 2 mm and a UL94 classification of V0, the weight percentages being based on the total composition obtained; The ratio of the amount of (meth)acrylate copolymer in weight percent to the amount of phosphorus-containing flame retardant in weight percent is 2.5 or less, and the ratio of the amount of (meth)acrylate copolymer in weight percent to the amount of polytetrafluoroethylene in weight percent is 20 or less, use.

[0170] 28. An EE assembly including an EE part according to any of embodiments 20-26, the EE assembly having an IP6K9K degree of protection according to ISO 20653:2013-02.

[0171] 29. The thermoplastic composition according to any one of embodiments 1 to 13, the molded article according to any one of embodiments 14 to 19, the EE part according to any one of embodiments 20 to 26, the use according to embodiment 27, or the EE assembly according to embodiment 28, wherein the aromatic polycarbonate is a bisphenol A-based homopolycarbonate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS EXAMPLES

[0172] 1. Description of raw materials and testing methods a) Raw materials Component A-1: ​​A linear polycarbonate based on bisphenol A, which has a melt volume flow rate of 12 cm 3 / (10 min) (according to ISO 1133:2012-03 at a test temperature of 300° C. and a load of 1.2 kg) and contains 250 ppm (=0.025% by weight, based on the total weight of component A) of triphenylphosphine heat stabilizer as component E-3.

[0173] Component A-2: A linear polycarbonate based on bisphenol A, which has a melt volume flow rate of 6 cm 3 / (10 min) (in accordance with ISO 1133:2012-03 at a test temperature of 300°C and a load of 1.2 kg).

[0174] Component B-1: (meth)acrylate copolymer, available from Mitsubishi Rayon under the trade name Metablen H-881, which contains about 10% by weight of an aromatic acrylate component.

[0175] Component C-1: Organic phosphate ester of formula (12), q=1.0 to 1.2. Bisphenol A bis(diphenyl phosphate), manufactured by ADEKA Corporation.

[0176] Component C-2: Rabitle FP110 phenoxycyclophosphazene, manufactured by Fushimi Pharmaceutical Co., Ltd. (Japan), formula (13g), trimer ratio (k=1) is approximately 68 mol%.

[0177] Component C-3 * : potassium perfluoro-1-butanesulfonate, commercially available as Bayowet™ C4 from Lanxess AG, Leverkusen, Germany, CAS number 29420-49-3.

[0178] Component D-1: ADS5000 SAN encapsulated polytetrafluoroethylene (approximately 50% by weight PTFE (a fluorine-containing anti-drip agent) and approximately 50% by weight SAN), manufactured by Chemical Innovation Co., Ltd. Thailand.

[0179] Component D-2: Teflon CFP6000X polytetrafluoroethylene, manufactured by Chemours Netherlands BV.

[0180] Component E-1: Mold release agent. Pentaerythritol tetrastearate, commercially available as Loxiol VPG 861 from Emery Oleochemicals Group.

[0181] Component E-2: Mixture of heat stabilizers and antioxidants. Irganox® B900 from BASF (a 4:1 weight ratio mixture of Irgafos® 168 (tris(2,4-di-tert-butylphenyl) phosphite) and Irganox® 1076 (octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate)).

[0182] b) Test method Comparative Tracking Index (CTI): For the purpose of determining the comparative tracking index, the compositions described herein were tested according to the rapid test method according to IEC 60112:2009. For this purpose, a 0.1% ammonium chloride test solution (395 ohm·cm resistivity) was dropped onto the surface of a test specimen with dimensions 60 mm×40 mm×4 mm, between two adjacent electrodes spaced 4 mm apart, with a time interval of 30 seconds. A test voltage was applied between the electrodes and varied over the course of the test. The first test specimen was tested with a starting voltage of 300 V or 350 V. A maximum of 50 drops in total per voltage (one drop every 30 seconds) were dropped as long as no tracking current of more than 0.5 A occurred for 2 seconds or the specimen did not burn. After 50 drops, the voltage was increased by 50 V and a new specimen was tested at this increased voltage according to the procedure described above. This process continued until either 600 V was reached or a tracking current or burning occurred. If one of the above effects occurred already in less than 50 drops, the voltage was reduced by 25V and a new specimen was tested at this reduced voltage. The voltage was reduced until the test completed 50 drops without causing tracking current or burning. Thus, this procedure was used to identify the maximum possible voltage at which the composition could withstand 50 drops of test solution without causing tracking current. Finally, for confirmation, four more specimens were tested with 50 drops each at the maximum voltage specified. This confirmed value was reported as the CTI in the examples. The 100 drop value was not specified because it was a "rapid test method based on" the specified standard.

[0183] PTI (Guaranteed Tracking Index): PTI is tested according to IEC 60112:2009 with the following modifications. For this purpose, a 0.1% ammonium chloride test solution (395 ohm cm resistivity) is dropped onto the surface of a specimen with dimensions 60 mm x 40 mm x 4 mm, between two adjacent electrodes spaced 4 mm apart, with a time interval of 30 seconds. In contrast to the CTI test, in the PTI test a constant test voltage is applied between the electrodes, and a total of five specimens are tested at each voltage. A maximum of 50 drops in total (one drop every 30 seconds) are dropped per specimen, as long as no tracking current of more than 0.5 A occurs for 2 seconds or the specimen does not burn.

[0184] Flame Retardant: The flame retardancy of polycarbonate compositions was tested at a thickness of 2 mm according to Underwriters Laboratories method UL 94 V. The assigned flammability classes are based on standard conditioned individual tests of 48 and 168 hours.

[0185] Depending on the behavior of the specimens, they are assigned to various flammability classes, including time to flame extinguish, drip resistance, or whether the material produces flammable drips. Hereinafter, the identified classes will be designated V0, V1, and V2. These are established based on a total of five specimens tested.

[0186] V0: A specimen that, when placed at 180° (perpendicular) with its long axis to the flame, has an average afterflame time of 10 seconds or less after the flame is removed and does not produce any drips of plastic particles that ignite cotton wool placed under the specimen. The total afterflame time with two applications of the flame to each of the five specimens is a maximum of 50 seconds.

[0187] V1: In contrast to V0, the average maximum afterflame time in this case is less than 30 seconds, but again no ignition of dripping particles or cotton wool is permitted. The total afterflame time with two flame applications to each of the five specimens is less than 250 seconds.

[0188] V2: In contrast to V0 and V1, this classification results in the formation of drips of plastic particles which ignite the cotton wool. The individual afterflame times are less than 30 seconds and the total afterflame time of two flame applications to each of the five specimens is less than 250 seconds.

[0189] f.: If the afterflame time exceeds the above, the test does not assign a flame retardant rating.

[0190] Heat Distortion Resistance: The heat distortion resistance of the compositions was determined on test specimens with dimensions 80 mm x 10 mm x 4 mm based on the Vicat softening temperature (Method B, test force 50 N, heating rate 50 K / h) according to ISO 306:2014-3.

[0191] 2. Preparation of Test Specimens The compositions were prepared in a Coperion 25 mm twin screw extruder with a throughput of 20 kg / h. The temperature of the polymer melt in the extruder was 260° C.-280° C. and the average screw speed was 225 rpm.

[0192] Test specimens measuring 60mm x 40mm x 4mm were produced from the molding compound using standard injection molding techniques with a melt temperature of 280°C and a mold temperature of 80°C.

[0193] 3.Results In the table below, "nt." means "not tested" and "f." means "failed." * " means "obtained from UL Yellow Card."

[0194] [Table 1]

[0195] Tables 1 to 3 include polycarbonate compositions containing 5% to 20% by weight of polymethacrylate copolymer B-1. For polycarbonates with an inherently low comparative tracking index, even small amounts of component B-1 surprisingly improve the comparative tracking index significantly (see V-2 and V-3). That the compositions have a robust comparative tracking index is demonstrated by passing the PTI test in the medium voltage range of 300V to 350V. This range is particularly important and is usually the reason for failure in the CTI test. If a material can successfully pass this voltage range, the probability of a high CTI, for example of 600V, is very high. However, a V0 classification according to UL94 at 2mm can only be achieved by the addition of additional flame retardants and anti-drip agents (E-4 to E-6). Even higher amounts of polymethyl methacrylate copolymer B-1 have a positive effect on the CTI (see Table 2), where the importance of the flame retardant selection is clearly evident from Comparative Examples V-8 and V-9. *) even in very small amounts results in failure of the material in the CTI test. Higher amounts of otherwise suitable phosphorus-based flame retardants (components C-1 and C-2) have a negative effect on the CTI (see V-17 and V-22). It is also clearly evident from the results in Table 2 that V0 classification according to UL94 cannot be achieved without the addition of an anti-drip agent (see V-11, V-15, V-18, V-20) and cannot be achieved by adding higher amounts of flame retardants (see V-17 and V-22). The optimum amount of anti-drip agent depends on the amount of polymethylmethacrylate copolymer B-1. Higher amounts of polymethylmethacrylate copolymer generally require more PTFE-containing anti-drip agent (see, for example, E-5 vs. V-12 and E-13). With a PMMA content of 10 wt%, 1 wt% PTFE (component D-2) or correspondingly 2 wt% 50:50 PTFE:SAN masterbatch D-1 is required for V0 classification (see E-13 to E-21). The optimum amount of flame retardant is above 2 wt% and below 12 wt% as shown above, with the heat distortion resistance decreasing as the amount increases. With the amount of polymethylmethacrylate copolymer in the range of 20 wt%, it becomes increasingly difficult to sufficiently flame retard the composition, and there is an obvious impact on the heat distortion resistance (see Table 3).

[0196] [Table 2]

[0197] [Table 3]

Claims

1. 1. A thermoplastic composition comprising: A) at least 68% by weight of an aromatic polycarbonate; B) 4% to 25% by weight of a (meth)acrylate copolymer comprising aromatic (meth)acrylate units b1 and methyl methacrylate units b2 in a weight ratio b1 / b2 of (5% to 20% by weight) / (80% to 95% by weight), based on the total weight of the (meth)acrylate copolymer; C) 2% to 10% by weight of a phosphorus-containing flame retardant; D) 0.25% to 2% by weight of a fluorine-containing anti-drip agent containing polytetrafluoroethylene; Contains The weight percentages are based on the total composition; the ratio of the amount of (meth)acrylate copolymer in weight percent to the amount of phosphorus-containing flame retardant in weight percent is less than or equal to 2.5, and the ratio of the amount of (meth)acrylate copolymer in weight percent to the amount of polytetrafluoroethylene in weight percent is less than or equal to 20; The thermoplastic composition does not contain a flame retardant selected from the group consisting of alkali metal salts, alkaline earth metal salts and ammonium salts of aliphatic or aromatic sulfonic acid, sulfonamide and sulfonimide derivatives. Thermoplastic composition.

2. The thermoplastic composition of claim 1, wherein the amount of the phosphorus-containing flame retardant is from 2% to 8% by weight.

3. The thermoplastic composition according to claim 1 or 2, wherein the aromatic polycarbonate is a bisphenol A homopolycarbonate.

4. The thermoplastic composition according to any one of claims 1 to 3, wherein the composition contains from 5% to 20% by weight of a (meth)acrylate copolymer.

5. The thermoplastic composition of any one of claims 1 to 4, wherein the phosphorus-containing flame retardant is an organophosphate ester, a phosphazene, or a mixture thereof.

6. As phosphorus-containing flame retardants there are phosphazenes of formula (13g): 【Chemistry 1】 wherein k=1, 2, or 3, including mixtures thereof; The thermoplastic composition according to any one of claims 1 to 5.

7. As phosphorus-containing flame retardants, there are organic phosphate esters of formula (11): 【Chemistry 2】 During the ceremony, R 1 , R 2 , R 3 , and R 4 are each independently a straight or branched chain C 1 ~C 8 - alkyl radicals and / or optionally linear or branched alkyl substituted C 5 ~C 6 -cycloalkyl radical, C 6 ~C 10 -aryl radical, or C 7 ~C 12 - an aralkyl radical, n is independently 0 or 1; q is independently 0, 1, 2, 3, or 4; N is a number from 1 to 30, R 5 and R 6 are independently linear or branched chain C 1 ~C 4 - an alkyl radical, preferably a methyl radical, Y is a linear or branched chain C 1 ~C 7 -Alkylidene, linear or branched chain C 1 ~C 7 - alkylene radical, C 5 ~C 12 -cycloalkylene radical, C 5 ~C 12 -Cycloalkylidene radical, -O-, -S-, -SO-, SO 2 or -CO-; The thermoplastic composition according to any one of claims 1 to 6.

8. Optionally, E) one or more additional additives selected from the group consisting of one or more mold release agents, heat stabilizers, antioxidants, dyes, pigments, ultraviolet absorbers, infrared absorbers, impact modifiers, antistatic agents, optical brighteners, hydrolysis stabilizers, ester interchange stabilizers, compatibilizers, laser marking additives, and mixtures thereof; Also contains The thermoplastic composition according to any one of claims 1 to 7, wherein the composition consists only of components A to D and optionally E.

9. The thermoplastic composition of any one of claims 1 to 8, wherein the thermoplastic composition also contains, in addition to Component A, Component B, Component C, and Component D, independently one or more heat stabilizers, antioxidants, mold release agents, dyes, pigments, and mixtures thereof.

10. A molded article consisting of the thermoplastic composition according to any one of claims 1 to 9 or comprising a region made of the thermoplastic composition according to any one of claims 1 to 9.

11. 11. The molding of claim 10, wherein the molding is a part of a high voltage switch, an inverter, a relay, an electronic connector, an electrical connector, a circuit breaker, a solar power system, an electric motor, a heat sink, an electric vehicle charger and charging plug, an electrical junction box, a smart meter housing, a miniature circuit breaker, or a busbar.

12. EE part comprising a moulding according to claim 10 or 11 or a layer made of the thermoplastic composition according to any one of claims 1 to 9.

13. a first conductor and a second conductor at a first distance d1 and a second distance d2 from each other; Including, They are connected via the thermoplastic composition according to any one of claims 1 to 10, the thermoplastic composition being in direct contact with the first electrical conductor and the second electrical conductor; the distance d1 is the shortest distance between the first and second electrical conductors along a surface of the thermoplastic material M; the distance d2 is the shortest distance between the first conductor and the second conductor through air, d2 is selected to prevent sparks through the air at each operating voltage; d1 is, at the working voltage U listed below, d1i (0V≦U≦250V): 1.3mm~<2.5mm d1ii (250V<U≦500V)=2.5mm~<5.0mm d1iii (500V<U≦1000V)=5.0mm~<10.0mm 13. The EE part of claim 12, wherein:

14. To achieve a CTI of 600V and a UL94 classification of V0 as specified according to IEC 60112:2009 at 2 mm in a thermoplastic aromatic polycarbonate-based composition, 4% to 25% by weight of a (meth)acrylate copolymer comprising aromatic (meth)acrylate units b1 and methyl methacrylate units b2 in a weight ratio b1 / b2 of (5% to 20% by weight) / (80% to 95% by weight), based on the total weight of the (meth)acrylate copolymer; 2% to 10% by weight of a phosphorus-containing flame retardant; 0.25% to 2% by weight of a fluorine-containing anti-drip agent containing polytetrafluoroethylene; The use of a combination of The weight percentages are based on the total composition. the ratio of the amount of (meth)acrylate copolymer in weight percent to the amount of phosphorus-containing flame retardant in weight percent is less than or equal to 2.5, and the ratio of the amount of (meth)acrylate copolymer in weight percent to the amount of polytetrafluoroethylene in weight percent is less than or equal to 20; use.